Taxonomic similarity does not predict necessary sample size for ex situ conservation: a comparison among five genera. Issue 1926 (13th May 2020) - Hoban, Sean; Callicrate, Taylor; Clark, John; Deans, Susan; Dosmann, Michael; Fant, Jeremie; Gailing, Oliver; Havens, Kayri; Hipp, Andrew L.; Kadav, Priyanka; Kramer, Andrea T.; Lobdell, Matthew; et al.
Abstract : Effectively conserving biodiversity with limited resources requires scientifically informed and efficient strategies. Guidance is particularly needed on how many living plants are necessary to conserve a threshold level of genetic diversity in ex situ collections. We investigated this question for 11 taxa across five genera. In this first study analysing and optimizing ex situ genetic diversity across multiple genera, we found that the percentage of extant genetic diversity currently conserved varies among taxa from 40% to 95%. Most taxa are well below genetic conservation targets. Resampling datasets showed that ideal collection sizes vary widely even within a genus: one taxon typically required at least 50% more individuals than another (though Quercus was an exception). Still, across taxa, the minimum collection size to achieve genetic conservation goals is within one order of magnitude. Current collections are also suboptimal: they could remain the same size yet capture twice the genetic diversity with an improved sampling design. We term this deficiency the 'genetic conservation gap'. Lastly, we show that minimum collection sizes are influenced by collection priorities regarding the genetic diversity target. In summary, current collections are insufficient (not reaching targets) and suboptimal (not efficiently designed), and we show how improvements can be made.